Inhibition shapes selectivity to vocalizations in the inferior colliculus of awake mice - Mayko, Zachary; Roberts, Patrick D.; Portfors, Christine (Frontiers in Neural Circuits, 2012)
The inferior colliculus (IC) is a major center for integration of auditory information as it receives ascending projections from a variety of brainstem nuclei as well as descending projections from the thalamus and auditory cortex. The ascending projections are both excitatory and inhibitory and their convergence at the IC results in a microcircuitry that is important for shaping responses to simple, binaural, and modulated sounds in the IC. Here, we examined the role inhibition plays in shaping selectivity to vocalizations in the IC of awake, normal-hearing adult mice (CBA/CaJ strain). Neurons in the IC of mice show selectivity in their responses to vocalizations, and we hypothesized that this selectivity is created by inhibitory microcircuitry in the IC. We compared single unit responses in the IC to pure tones and a variety of ultrasonic mouse vocalizations before and after iontophoretic application of GABAA receptor (GABAAR) and glycine receptor (GlyR) antagonists. The most pronounced effects of blocking GABAAR and GlyR on IC neurons were to increase spike rates and broaden excitatory frequency tuning curves in response to pure tone stimuli, and to decrease selectivity to vocalizations. Thus, inhibition plays an important role in creating selectivity to vocalizations in the inferior colliculus.